Penggunaan Modifikasi Permainan Congklak Untuk Meingkatkan Kecepatan Menghitung Dalam Operasi Penjumlahan Bilangan Bulat Pada Siswa Kelas I SD Negeri 060886 Medan Tahun Ajaran 2017/2018 - Agustina Ginting (Keguruan, 2021)
This study aimed to obtain and improve the learning outcomes of Mathematics about the addition of integers toward the first grade students in SD Negeri 060886 Medan. The approach used is a qualitative approach with the type of classroom action research. The number of students who were joined as research subjects were 20 students.This paper occured based on the introspection of the author after student learning on the material about Integers with the indicator of performing arithmetic operations toward the addition of integers by using a number line. After they studied according to the available time allocation, it turned out that the results of the assessment were not satisfactory. The author suspected that the using of a number line in the operation of adding integers makes students bored and makes learning process become less interesting. Based on the introspection above, the author creates tools/media that are expected to make students easier to understand the material, be active, creative, affective and fun; namely the modification of Congklak Game. The results showed that the average value of Mathematics Learning Outcomes in the Pre-Cycle was 4.5 and increased into 6.3 in Cycle I; and increased into 9.15 in Cycle II. It can be concluded that by using a modified game of Congklak can increase the speed of counting in integer addition operations.